Literature Review of the Agricultural Distribution Services Sector: Performance, Efficiency and Research Issues - Ponciano S. Intal; Luis Osman Ranit (Philippine Institute for Development Studies (PIDS), 2001)
This literature review characterizes the structure and performance of the agricultural distribution sector in the Philippines. Drawing from previous studies, it describes agricultural marketing in the country as a complex and fragmented system. The paper looks at several models that deal with market integration and price correlations, and emphasizes the urgency of applying these methods in analyzing different commodity markets in the country. Based on the existing literature, it discusses issues such as price margins, monopoly power in agricultural distribution, transportation, infrastructure, and technology. Finally, it presents a number of major research gaps and corresponding suggestions for research.
Keywords: 330; agricultural distribution sector; agricultural market; agricultural performance; distribution channels; literature review; Agrarmarkt; Logistik; Philippinen